1994
DOI: 10.7863/jum.1994.13.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasonographic analysis of the normal postpartum uterus: technique, variability, and measurements.

Abstract: We evaluated normal uterine involution prospectively with real-time ultrasonography in 100 women after uncomplicated term vaginal delivery. Transducers easily distorted the spongy uterus during early postpartum scanning, an effect minimized with sector transducers that are superior to linear or convex probes for accurate early postpartum uterine measurement. Long-axis measurements correcting for uterine angulation were the most reproducible and accurate, irrespective of bladder distention. Uterine T o our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 2 publications
(5 reference statements)
1
39
0
Order By: Relevance
“…Sonography is frequently used during pregnancy to image shape. Wachsberg et al [6] sonographically evaluated normal uterine involution in 100 women after uncomplicated term vaginal delivery. They found that uterine involution was unrelated to the infant's birth weight and breast-feeding, although higher parity was associated with slightly larger uterine dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Sonography is frequently used during pregnancy to image shape. Wachsberg et al [6] sonographically evaluated normal uterine involution in 100 women after uncomplicated term vaginal delivery. They found that uterine involution was unrelated to the infant's birth weight and breast-feeding, although higher parity was associated with slightly larger uterine dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Wachsberg et al [3] sonographically evaluated normal uterine involution in 100 women after uncomplicated term vaginal delivery. They found that uterine involution was unrelated to the infant's birth weight and breast-feeding, although higher parity was associated with slightly larger uterine dimensions up to 4 weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding appears to be the most widely studied of these factors with regard to its effects on uterine involution (Bruce et al, 1991;Galli et al, 1993;Wachsberg et al, 1994;Cluett et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Several factors have been suggested as having an effect on the rate of uterine involution including breastfeeing (Galli et al, 1993;Wachsberg et al, 1994;Cluett et al, 1997), parity (Galli et al, 1993;Wachsberg et al, 1994), caesarean section (Galli et al, 1993) premature rupture of the membranes (Tsenov and Krusteva, 1995) and infant birth weight (Wachsberg et al, 1994). Breastfeeding appears to be the most widely studied of these factors with regard to its effects on uterine involution (Bruce et al, 1991;Galli et al, 1993;Wachsberg et al, 1994;Cluett et al, 1997).…”
Section: Introductionmentioning
confidence: 99%